Protozoan parasite Toxoplasma gondii manipulates mate choice in rats by enhancing attractiveness of males. - Shantala Arundathi Hari Dass; Anand Vasudevan; Deborah Dutta; Linda Jing Ting Soh; Robert Morris Sapolsky; Ajai Vyas (PLoS ONE, 2011)
Females in various species typically avoid males infected with parasites, while parasite-free males advertise their status through conspicuous phenotypic traits. This process selects for heritable resistance and reduces direct exposure of the female to parasites. Coevolving parasites are likely to attempt to circumvent this obstacle. In this paper, we demonstrate a case of parasitic manipulation of host mate choice. We report that Toxoplasma gondii, a sexually transmitted infection of brown rats, enhances sexual attractiveness of infected males. Thus under some evolutionary niches, parasites can indeed manipulate host sexual signaling to their own advantage.